2015
DOI: 10.1590/s1984-82502015000300004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety and tolerability of L-3-n-butylphthalide tablet after single and multiple oral administrations in healthy Chinese volunteers

Abstract: L-3-n-butylphthalide (L-NBP) is a naturally occurring antioxidant, which can be used for the treatment of acute ischemic stroke and vascular dementia. This study evaluated the safety, tolerability and pharmacokinetics of L-NBP tablets in healthy Chinese volunteers. This was a single-center, randomized, double-blind, placebo-controlled, single-and multiple-dose study. Subjects were assigned to receive a single dose of L-NBP tablet at either 80, 160, 320, or 480 mg (n=40), or multiple doses of 160 mg twice daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Extensive experimental and clinical studies have furthermore confirmed those properties leading to the approval and marketing of dl-NBP as an anti-ischemic drug in China since 2002. Several studies focused on the human metabolism and pharmacokinetics of NBP showed that NBP is safe for human usage [4] and that it essentially undergoes oxidation by cytochrome P450 (P450) after oral administration, resulting in 23 identified metabolites, among which 10-keto-NBP (M2), 3-hydroxy-NBP (M3-1), 10-hydroxy-NBP (M3-2), and NBP-11-oic acid (M5-2) are considered as major metabolites [5, 6]. Those studies also established that hydroxylation of the n-butyl side chain and C-3 constitutes the main metabolic route and that urine is the main excretion pathway of dl-NBP metabolites [6].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experimental and clinical studies have furthermore confirmed those properties leading to the approval and marketing of dl-NBP as an anti-ischemic drug in China since 2002. Several studies focused on the human metabolism and pharmacokinetics of NBP showed that NBP is safe for human usage [4] and that it essentially undergoes oxidation by cytochrome P450 (P450) after oral administration, resulting in 23 identified metabolites, among which 10-keto-NBP (M2), 3-hydroxy-NBP (M3-1), 10-hydroxy-NBP (M3-2), and NBP-11-oic acid (M5-2) are considered as major metabolites [5, 6]. Those studies also established that hydroxylation of the n-butyl side chain and C-3 constitutes the main metabolic route and that urine is the main excretion pathway of dl-NBP metabolites [6].…”
Section: Introductionmentioning
confidence: 99%
“…[27] As stated, in 2002, NBP was approved by the China Food and Drug Administration for clinical trials for the treatment of cerebral ischemia. [28] According to the results of a recent clinical trial, the efficiency of NBP for the treatment of ischemic cerebrovascular disease is as high as 74.7%, with a low incidence of adverse reactions. [29] Further, a series of studies has shown that NBP is safe for clinical treatment.…”
Section: Butylphthalide and Strokementioning
confidence: 99%
“…The compound 3- n -butylphthalide is a biologically active lactone found in plants from the celery family [ 11 , 12 ]. Originally an ingredient in traditional Chinese medicine, it was accepted in China as a drug for cerebral ischemic stroke that improves the neurological function of the patients [ 13 , 14 , 15 ]. The compound restores microcirculation and protects the mitochondria.…”
Section: Introductionmentioning
confidence: 99%